Neurodevelopmental outcome of babies with moderate to severe birth asphyxia with hypoxic ischemic encephalopathy treated with and without therapeutic hypothermia followed up till 6-24 month of age at tertiary care hospital of Southern Rajasthan - Kachhwaha, Ritika; Goyal, Suresh; Mehrotra, Juhi; Sethia, Sakshi; G. M., Jeevan (International Journal of Contemporary Pediatrics, 2023)
hypoxic ischemic encephalopathy. There are very few studies comparing the neurodevelopmental outcomes in neonates with moderate to severe HIE who received and not received TH. Objective was assessment of neurodevelopmental outcome between TH and non-TH group till last follow-up. Methods: Hospital Based Prospective study. All term neonates with Moderate to severe birth asphyxia with HIE who received TH and not received TH, admitted in NICU of BalChikitsalay, RNTMC, Udaipur, consenting for the study were followed up at age 3-6 month, 6-12 month, 12-18 month and 18-24 month from September 2018 to February 2021 and neurodevelopment outcome was assessed. Results: 70 neonates with birth asphyxia HIE II / III were included in the study, 35 in TH group and 35 in non-TH group. Out of 70 babies enrolled 46 (65.7%) were having normal development and 24 (34.3%) were having development delay. Out of 46 who were having development delay 6 (17.4%) were of TH group and 18 (51.4%) were of non-TH group. Most of the babies of TH group i.e., 30 (85.7%) were neurodevelopmentally normal and 5 (14.3%) were having some neurodevelopmental abnormality. In non-TH group 15 (42.8%) were normal and 20 (57.2%) were having some neurodevelopmental abnormality. Conclusions: Results of the study showed significantly better outcome in infant who received therapeutic hypothermia than those who did not.